2020
DOI: 10.1177/0748730420927601
|View full text |Cite
|
Sign up to set email alerts
|

Short Sleep Duration and Extremely Delayed Chronotypes in Uruguayan Youth: The Role of School Start Times and Social Constraints

Abstract: During adolescence, biological, psychosocial, and contextual factors converge in a “perfect storm” and have been put forward to explain the delay in chronotype observed at this age and the prevalence of disrupted sleep. This study provides evidence to support that chronotype and sleep patterns (particularly sleep duration) are socially constrained and to identify novel significant social predictors. Uruguayan public school activities are arranged in up to 4 shifts, creating a natural experiment to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 101 publications
2
50
2
Order By: Relevance
“…From the point of view of the regulation of sleep by homeostatic and circadian factors [ 32 , 33 ], as in the two-process model, we expect low levels of evening sleepiness not only to lead to later bedtimes, but also, because of the circadian regulation of sleep timing and duration [ 32 , 33 ], we expect later bedtimes to be associated with shorter sleep durations. Later bedtimes should also lead to shorter sleep durations due to social constraints such as the need to get up for work or school [ 34 ]. Short sleep duration will lead to higher levels of sleepiness in the morning and continue to be elevated until the next evening.…”
Section: Introductionmentioning
confidence: 99%
“…From the point of view of the regulation of sleep by homeostatic and circadian factors [ 32 , 33 ], as in the two-process model, we expect low levels of evening sleepiness not only to lead to later bedtimes, but also, because of the circadian regulation of sleep timing and duration [ 32 , 33 ], we expect later bedtimes to be associated with shorter sleep durations. Later bedtimes should also lead to shorter sleep durations due to social constraints such as the need to get up for work or school [ 34 ]. Short sleep duration will lead to higher levels of sleepiness in the morning and continue to be elevated until the next evening.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies found similar effects only when school started much later, such as in the afternoon [61,62].…”
Section: Discussionmentioning
confidence: 64%
“…Double-blinding, the gold standard in terms of evidence level, is, of course, inherently unfeasible in this context, and it seems almost impossible to convince schools to participate in randomization [36]. Although there are some real-life settings, such as in Uruguay or Argentina, where students are randomly assigned to morning, middle, and afternoon school shifts [37,38], this is not the case in most other countries around the world. The few longitudinal studies that exist often covered ≤6 months in their follow-ups [30] (but see [39][40][41][42][43]), and are thus prone to seasonal confounding.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, we highlight that current early school start times around the globe are detrimental for sleep and health and likely do not allow students to excel as much as they could. Many studies have shown positive effects on sleep or well-being, when school starts were delayed [21][22][23][24] or in systems were school already starts much later, such as in Uruguay or Argentina [76,77]. Thus, it seems fair to argue that later starts are beneficial for students in terms of health and well-being.…”
Section: Discussionmentioning
confidence: 99%